2004
DOI: 10.1056/nejmoa040331
|View full text |Cite|
|
Sign up to set email alerts
|

A Randomized Trial of Exemestane after Two to Three Years of Tamoxifen Therapy in Postmenopausal Women with Primary Breast Cancer

Abstract: Tamoxifen, taken for five years, is the standard adjuvant treatment for postmenopausal women with primary, estrogen-receptor-positive breast cancer. Despite this treatment, however, some patients have a relapse. methodsWe conducted a double-blind, randomized trial to test whether, after two to three years of tamoxifen therapy, switching to exemestane was more effective than continuing tamoxifen therapy for the remainder of the five years of treatment. The primary end point was disease-free survival. resultsOf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
868
3
29

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,629 publications
(926 citation statements)
references
References 32 publications
20
868
3
29
Order By: Relevance
“…The fracture rate of letrozole-treated patients in the MA-17 trial was 3.6% versus 2.9% in placebo, following 5 years of tamoxifen treatment [95]. Similar small increases in osteoporosis and/or fractures (7.41%) were associated with the steroidal aromatase inhibitor, exemestane compared to tamoxifen (5.7%) in the IES trial [96].It is suggested that patients are evaluated for baseline bone mineral density and receive bisphosphonate therapy if indicated [99]. No significant changes in serum cholesterol, HDL cholesterol, LDL Cholesterol, triglycerides or Lp(a) occur in non-hyperlipidemic postmenopausal women treated for three years following five years of adjuvant tamoxifen [100].…”
mentioning
confidence: 86%
“…The fracture rate of letrozole-treated patients in the MA-17 trial was 3.6% versus 2.9% in placebo, following 5 years of tamoxifen treatment [95]. Similar small increases in osteoporosis and/or fractures (7.41%) were associated with the steroidal aromatase inhibitor, exemestane compared to tamoxifen (5.7%) in the IES trial [96].It is suggested that patients are evaluated for baseline bone mineral density and receive bisphosphonate therapy if indicated [99]. No significant changes in serum cholesterol, HDL cholesterol, LDL Cholesterol, triglycerides or Lp(a) occur in non-hyperlipidemic postmenopausal women treated for three years following five years of adjuvant tamoxifen [100].…”
mentioning
confidence: 86%
“…Compared with women assigned to treatment with placebo or tamoxifen, those treated with aromatase inhibitors have consistently shown higher rates of arthralgia. In trials of women with advanced breast cancer, arthralgias have been more common in women treated with aromatase inhibitors than in the comparator group despite their lower rates of metastases, which might also cause bone pain (20)(21)(22)(23)(24).…”
Section: Evidence Linking Pharmacologically Induced Low Estrogen Levementioning
confidence: 99%
“…The Arimidex, Tamoxifen, Alone or in Combination (ATAC) trial showed that anastrozole, given from diagnosis for 5 years, improved disease-free survival by 4.1% compared to 5 years tamoxifen (100 months median follow up data) [1]. Other adjuvant aromatase inhibitors studies have shown similar benefits [2][3][4]. These strategies, although initially expensive, reduce the risk of relapse and hence involve long-term cost savings [5].…”
Section: Introductionmentioning
confidence: 99%
“…Health economic analyses of anastrozole have been conducted in the past [6], but all estimate the cost of a relapse using predictive modelling, questionnaires or interviews with clinicians [2,3,[7][8][9]]. An independent United Kingdom (UK) trial, now 6 years old, estimated hospital costs of relapsed breast cancer by sending questionnaires to UK oncologists, and estimated a cost of £12,500 per patient [10,11].…”
Section: Introductionmentioning
confidence: 99%